Émergence de la notion de service environnemental et des dispositifs de rémunération des fournisseurs: le cas du Cambodge - Colas Chervier; Christophe Déprés; Malyne Neang (VertigO, 2012)
The definition of environmental policies in developing countries is affected by globalization of such issues and the change in governments’ interventions. Based on regulatory approaches for ages, environmental policy tends nowadays to promote more incentive tools called market-bases instruments.This article aims at illustrating the trend in Cambodia from data field surveys conducted in 2010 with a sample of local stakeholders: policy makers, NGO officers and donors. The objective is to understand the emergence of the pair of notions eco-system services (ES) and payment for environmental services (PES) in conservation policies implemented in the country (areas of biodiversity and carbon sequestration mainly) and international influence in this process.The paper shows that the initial conservation strategies based on regulatory approaches with the establishment of protected areas, have had mixed success in particular to reduce deforestation. Over the recent years, the concept of SE has been quickly circulated within government offices (Forestry Administration, Ministry of Environment). Number of conservation projects conducted by international NGOs (such as CI, WCS) has also sought to recognize the value of protected ecosystems. In this objective, they have experienced payment devices to rural/forest communities sitting on environmentally-friendly practices related to the conservation of fragile habitats. Cambodian legal framework has not yet recognized, so far, the concept of PES (based on the beneficiary pays principle) and significant obstacles remain in the development of such mechanisms on a large scale.